(untitled) (GEON Journal (Management, Organizations and Business), 2013)
The OM Market Orientation involves mixing two organizational aspects : the functional and strategic in two dimensions that typify , a cognitive character a dichotomy between philosophy / business culture aside , and knowledge / intelligence the other. The behavioral dimension is divided into a process-based perspective and based on the function / action as a mission of the OM , these processes require continuous innovation efforts in the marketing strategies of companies. The research was carried out under qualitative approach of grounded theory expression that involves the pursuit of theoretical models that account for the problems experienced by companies have a comprehensive character of the phenomenon to be studied and possible explanatory cause-effect relationships . relying on the induction and analysis method of the different pieces of information collected and the deduction hypothetical- factorial .